Simulation of Temperature Distribution in Horizontal Fin Heat Sink CPU Processor Using Comsol Multiphysics and Proportional Control - T.D. Sugiarto; R.F. Iskandar; Ismudiati Puri Handayani (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2015)
This research is aimed to analyze and simulate the temperature distribution in heat sink CPU processor. The study analyzes the heat absorption from the heat source to the bottom of the heat sink, the conduction process, and the forced convection process. All processes are simulated with software Comsol Multiphysics 4.4 to obtain the optimal heat sink design. The simulation is performed by varying the number of fins, the fin thickness, the air gap between two fins, the fin surface area, and the convection coefficient. The optimal design is found for heat sink with 40 pieces fins, fin thickness of 0.4 mm, air gap of 2.4 mm, fin surface area of 9425 mm2, and the convection coefficient of 5.26 W/m2K. Further simulation shows that PID control improved the forced convection process. A proportional control (P) is reasonable enough to achieve a settled convection process. A settling temperature occurs at 241 s after heat is applied to the system. This is faster than non-controlled convection process which requires 1600 s instead. Additional integration and derivative controls will increase stability at later time.